Analysis of Staphylococcus aureus infection and enterotoxin gene carriage in diarrhoeal patients in Jiading District, Shanghai - CHEN Peichao; HUANG Qiang; CHENG Fangzhou; CHEN Huijuan; MA Zhiqi; SUN Pan; PENG Qian (Shanghai yufang yixue)
ObjectiveTo investigate the prevalence of Staphylococcus aureus in patients with diarrhea, and to analyze the genes carriage of enterotoxin in the strains of these patients in Jiading District, Shanghai.MethodsFrom 2021 to 2023, anal swabs of diarrhea outpatients from one sentinel hospital and nine community health service centers in different townships in Jiading District, Shanghai, were tested for Staphylococcus aureus, from which five enterotoxin virulence genes such as SEA, SEB, SEC, SED, and SEE were tested simultaneously.ResultsA total of 1 080 anal swabs were collected, 81 of which were tested positive for S. aureus, with a detection rate of 7.50%, and the detection rate of S. aureus was similar in patients with diarrhea from 2021‒2023. There was no statistically significant difference in detection rates between males and females (χ2=0.821, P=0.365). S. aureus detection rate was highest in infants and young children with diarrhea (29.51%), followed by 14.06% in the people aged between 4‒<31 years, and 2.99% in those aged ≥31 years. Significant differences were observed in the detection rate of S. aureus in the diarrhoeal patients from different townships of Jiading District(χ2=66.134,P<0.05). The carriage rates of the 5 enterotoxin genes, namely SEA, SEB, SEC, SED, SEE, were 13.58%, 14.81%, 11.11%, 7.41%, and 0, respectively.ConclusionThe prevalence of S. aureus among the patients with diarrhea in Jiading District is relatively stable but with distinct geographical patterns. Children and adolescents are high-risk groups. SEB were the dominant gene, followed by SEA.